2019
DOI: 10.1038/s41418-019-0351-4
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA H19 initiates microglial pyroptosis and neuronal death in retinal ischemia/reperfusion injury

Abstract: Ischemia-reperfusion (I/R) is a common pathology when the blood supply to an organ was disrupted and then restored. During the reperfusion process, inflammation and tissue injury were triggered, which were mediated by immunocytes and cytokines. However, the mechanisms initiating I/R-induced inflammation and driving immunocytes activation remained largely unknown. In this study, we identified long non-coding RNA (lncRNA)-H19 as the key onset of I/R-induced inflammation. We found that I/R increased lncRNA-H19 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
167
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(175 citation statements)
references
References 53 publications
7
167
1
Order By: Relevance
“…The lncRNAs frequently form competing endogenous RNA (ceRNA) regulatory networks wherein they modulate the expression of downstream genes by competitively binding to microRNAs (miRNAs) 23 , 24 . CeRNA networks regulating pryoptosis have been reported in different cells types 25 , 26 , including neurons 27 . In this study, we screened differentially expressed lncRNAs and mRNAs between SCI group and sham-operated group, WT group and TLR4 −/− group using RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs frequently form competing endogenous RNA (ceRNA) regulatory networks wherein they modulate the expression of downstream genes by competitively binding to microRNAs (miRNAs) 23 , 24 . CeRNA networks regulating pryoptosis have been reported in different cells types 25 , 26 , including neurons 27 . In this study, we screened differentially expressed lncRNAs and mRNAs between SCI group and sham-operated group, WT group and TLR4 −/− group using RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“… 17 A recent report revealed that H19 regulated inflammation and nerve injury via directly sponging miR-21 to promote the expression of PDCA4 in retinal ischemia/reperfusion injury. 18 However, whether miR-21 could be regulated by H19 in children with asthma remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The biological importance of exosomes and exosomal-miRNA (exoMiR) is reflected by their association with a range of inflammatory ( Van Hezel et al, 2017 ; Cypryk et al, 2018 ), autoimmune ( Long et al, 2018 ; Anel et al, 2019 ) and neurodegenerative diseases ( Jan et al, 2017 ; Soria et al, 2017 ; Jain et al, 2019 ). These include diabetes ( Saeedi et al, 2018 ), rheumatoid arthritis ( Skriner et al, 2006 ; Zhang et al, 2006 ; Wan et al, 2019 ), and Alzheimer’s and Parkinson’s disease ( Gupta and Pulliam, 2014 ; Li et al, 2018 ; Jain et al, 2019 ; Sackmann et al, 2019 ). exoMiR have been reported to play pathogenic roles in these diseases by promoting angiogenesis ( Kosaka et al, 2013 ; Atienzar−Aroca et al, 2016 ), and modulating immune responses, including in the recruitment of immune cells ( Théry et al, 2002 ; Abusamra et al, 2005 ; Robbins and Morelli, 2014 ; Ye et al, 2014 ; Wong et al, 2016 ; Van Hezel et al, 2017 ); features that contribute to cell death.…”
Section: Introductionmentioning
confidence: 99%